Intersecting Laws: Analyzing the Tension Between Islamic Law and Positive Law on Child Marriage in Indonesia - Purnama, Dede Wahyu (Definisi: Jurnal Agama dan Sosial Humaniora, 2024)
This study aims to analyze the differences in perspectives between Islamic law and Indonesian positive law regarding the minimum age for child marriage and the social and legal implications of early marriage. This research uses a descriptive qualitative method with a literature study approach, collecting data from books, articles, journals, and relevant regulations. The findings reveal a significant difference between Islamic law, which offers flexibility in the marriage age limit, and Indonesian positive law, which sets stricter regulations on the minimum marriage age. The study also uncovers debates among scholars about the legitimacy of early marriage and the social and psychological impacts it causes. The contribution of this study lies in providing a deeper understanding of the interaction between religious norms and state law, as well as highlighting the importance of adjusting legal policies to social developments and human rights. This research also offers a new perspective on the discussion of early marriage in the context of modern society.